Everolimus in metastatic renal cell carcinoma patients intolerant to previous VEGFr-TKI therapy: a RECORD-1 subgroup analysis - Bracarda, S (Nature Publishing Group, 2012)
BACKGROUND: A relevant percentage of patients with metastatic renal cell carcinoma develop intolerance to vascular endothelial growth factor receptor-tyrosine kinase inhibitors (VEGFr-TKIs) and require careful selection of subsequent treatment. This retrospective analysis evaluated the safety and efficacy of everolimus in patients enrolled in the phase-III RECORD-1 trial who discontinued previous VEGFr-TKI therapy because of toxicity. METHODS: Patients with an adverse event (AE) as their primary reason for discontinuation of previous VEGFr-TKI therapy were included. Median progression-free survival (PFS) for VEGFr-TKI-intolerant patients in each arm was estimated using the Kaplan–Meier method, and effect on PFS (hazard ratio (HR)) was calculated using the Cox proportional hazard model. RESULTS: In VEGFr-TKI-intolerant patients (n=58, 14%), median PFS was 5.4 months with everolimus and 1.9 months with placebo (HR: 0.32; P=0.004). In sunitinib-intolerant patients (n=26), median PFS was 5.1 months with everolimus and 2.8 months with placebo (HR: 0.28; P=0.033). Grade 3/4 AEs reported with everolimus in VEGFr-TKI-intolerant patients included infections (16%), fatigue (7%) and stomatitis (4%). The toxicity profile of everolimus was similar in the VEGFr-TKI-intolerant and overall study populations. CONCLUSION: Everolimus is well tolerated and efficacious with no increased toxicity in patients intolerant to VEGFr-TKI therapy.